e-Learning resources for ophthalmologists - John Davis Akkara; Anju Kuriakose; Biju Raju (Kerala Journal of Ophthalmology, 2020)
The Internet has made information available and accessible by all. Specialized knowledge of all sorts is now available literally at one's fingertips. The students of today may actually learn more online than in a conventional classroom. This is true in the medical field and in ophthalmology as well. The vast amount of high-quality multimedia content helps to augment the understanding of the subjects. In this article, we discuss the various types of e-learning resources available to ophthalmologists at present and review a handful of the best online ophthalmology resources.